Understanding the Antecedents of Customer Loyalty in Network Airlines Industry in Klang Valley Area Malaysia - Angriado, Suci Lovena (2011)
Network airlines industry is considered as one of the most growing markets in the world. The objective of this research is to investigate the main factors that influencing customer loyalty among international students from any education institution in Klang Valley Area Malaysia. The main factors that are adopted in this research are brand name, perceived service quality, price and loyalty programs. Questionnaires are distributed to 200 international students and were used to analyze the results. The research result shows that price has a high influence on customer loyalty. The result also showed that overall factors have strong positive influence toward customer loyalty. Further recommendations and discussions of the results for further research are also provided.